Separatisme Etnis Bukan Sekedar Sebuah Wacana - Muhammad Idrus (Unisia, 2003)
An important step to attain goodprocess for nationai integrity is to demolish some negative aspects of cultural behavior. The autonomy must be put in the hand of local government, psychological gap among public servants, 'distance' between the leaders and ordinary people must be minimized. Beside debirocratization is a compulsory, legal certainty must be enforced. Indeed, the equal chance to get the rightsmust be available foreveryone.